2022
DOI: 10.1371/journal.pone.0262743
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of village fund and administrative capacity in stunting reduction: Empirical evidence from Indonesia

Abstract: The Indonesian government launched various programs to handle stunting cases, including village funds. This paper examined the effects of village fund programs and village apparatuses’ capacities to combat stunting based on aggregate data at the district level in Indonesia. Using descriptive data analysis and fixed effect panel regression, we observed that village fund programs could significantly reduce Indonesia’s stunting prevalence, especially outside Java. It also revealed that the increasing education of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
2
18
0
5
Order By: Relevance
“…After controlling for age, education, occupation, and years of experience, multivariate analysis reveals that the short course has a significant effect. Previous research showed that most cadres had good knowledge about the early detection of malnutrition in children [ 35 , 36 ]. Furthermore, the level of education also contributes to the increase in their capacity, knowledge, ability, and skills in monitoring growth and development [ 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After controlling for age, education, occupation, and years of experience, multivariate analysis reveals that the short course has a significant effect. Previous research showed that most cadres had good knowledge about the early detection of malnutrition in children [ 35 , 36 ]. Furthermore, the level of education also contributes to the increase in their capacity, knowledge, ability, and skills in monitoring growth and development [ 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers’ positive responses to home visit interventions motivate cadres, and the mutually reinforcing reciprocal relationship between cadres and mothers aids in the effective achievement of a reduction in stunting [ 6 ]. Obviously, stunting prevention measures require financial resources, which can be supplied from the village fund [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…to broader research, which creates ambiguity and variable insensitivity. Likewise, the involvement of the village fund budget requires a detailed, broad, and comprehensive analysis study from each village in their respective working areas 20 . It is because the nutrition care village is a part of community empowerment, in which empowerment is one of the objectives from the village fund.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Spending on stunting more than doubled after the 2014 Village Law was passed (Dirkareshza & Sihombing, 2021;Rossevelt, 2022). Preliminary comparisons of the 2016 village budget and 2019 village expenditures reveal that villages have increased their investment in stunting-related sectors (Indra & Khoirunurrofik, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Village-scale municipal governments are undertaking preventative measures (Indra & Khoirunurrofik, 2022). According to the Village Law, village authority in the APBDes (Village Revenue and Expenditure Budget) comprises the fields of village administration, village development implementation, community development, community empowerment, and unanticipated expenditures.…”
Section: Introductionmentioning
confidence: 99%